(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article focuses on the contribution of Professor K. Tynystanov to Kyrgyz terminology about the compilation of phonetic, lexical, grammatical (morphology, syntax) terms, and also discusses the scientific and theoretical and practical tasks of the Kyrgyz language, determining its role and meaning.